THE RIGHTS OF LAND IN MARRIAGE AGREEMENT ACCORDING TO THE CONSTITUTIONAL COURT DECISION NUMBER 69 / PUU-XIII 2015 BASED ON THE CUSTOMARY LAW PERSPECTIVE - Miqat, Nurul; Patittingi, Farida (Faculty of Law, Universitas Sebelas Maret, 2018)
The definition of marriage is provided in Article 1 that: